2008
DOI: 10.1093/treephys/28.10.1545
|View full text |Cite
|
Sign up to set email alerts
|

Variations in growth, survival and carbon isotope composition ( 13C) among Pinus pinaster populations of different geographic origins

Abstract: To evaluate differences in growth and adaptability of maritime pine (Pinus pinaster Ait.), we studied growth, polycyclism, needle tissue carbon isotope composition (delta(13)C) as an estimate of water-use efficiency (WUE) and survival of seven populations at 10 years of age growing in a performance trial at a provenance test site in Escaroupim, Portugal. Six populations were from relatively high rainfall sites in Portugal and southwestern France (Atlantic group), and one population was from a more arid Mediter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
68
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 32 publications
9
68
2
4
Order By: Relevance
“…Inter-and intra-population variation in δ 13 C δ 13 C variation between our populations was 1.26% in the xeric site and 0.60% in the mesic site, which is in the range of previous P. pinaster observations (Correia et al, 2008). As a result, we only found δ 13 C differentiation of populations in the xeric site (Tab.…”
Section: Carbon Isotope Compositioncontrasting
confidence: 55%
See 4 more Smart Citations
“…Inter-and intra-population variation in δ 13 C δ 13 C variation between our populations was 1.26% in the xeric site and 0.60% in the mesic site, which is in the range of previous P. pinaster observations (Correia et al, 2008). As a result, we only found δ 13 C differentiation of populations in the xeric site (Tab.…”
Section: Carbon Isotope Compositioncontrasting
confidence: 55%
“…Correia et al (2008) observed minor but significant δ 13 C differences between populations in a subhumid trial site. However, the populations from the driest and more humid origins displayed equal δ 13 C values, which is in agreement with our results in the mesic trial site.…”
Section: Carbon Isotope Compositionmentioning
confidence: 77%
See 3 more Smart Citations